Pengaruh Manajemen Peserta Didik Terhadap Prestasi Belajar Peserta Didik Madrasah Aliyah Negeri 1 Banyuwangi - Mamlukhah Mamlukhah; Amirotun Nahdliyah; Hanim Wafiroh (Institut Agama Islam Darussalam Blokagung, 2020)
This research is directed at 4 main points, namely a. To find out the application of the management of students of Madrasah Aliyah Negeri 1 Banyuwangi in the academic year2018 / 2019.b. To find out the learning achievement of students of Madrasah Aliyah Negeri 1 Banyuwangi in the academic year of2018 / 2019. c. To find out the effect of student management on the learning achievement of students of Madrasah Aliyah Negeri 1 Banyuwangi 2018/2019 academic year. d. To find out how much influence the management of students on the learning achievement of students of Banyuwangi State Islamic Senior High School 1 in 2018/2019. This research uses quantitative descriptive method with the technique of produc moment in the validity test and to find the reliability of the data using the alpha formula, while in the hypothesis test using the f test and t test then for the technique of data analysis using the normality test using the regression model. The population of this study is the 33 Madrasah Aliyah Negeri 1 Banyuwangi teacher's council. To measure the researchers' variable, the questionnaire was used to vary teaching methods of learning motivation. After analyzing the data collected, it was found that (1) the management of Madrasah Aliyah Negeri 1 Banyuwangi students was classified as good (2) the learning achievement of Madrasah Aliyah Negeri 1 Banyuwangi students was very good (3) there was an influence on the management of Madrasah students in Madrasah students Banyuwangi Aliyah Negeri 1 2018/2019 academic year is 95.4%. Key words: Student Management, Learning Achievement.